Research on software-defined network and the security defense technology - Tao WANG; Hong-chang CHEN; Guo-zhen CHENG (Tongxin xuebao)
Software-defined network (SDN) separated the traditional control plane from the data plane,formed a centralized controller,opened up the network programming interface,simplified network management,promoted network innovation and optimized network operation.However,SDN's “three-layer two-interface” architecture increased the network attack surface,resulting in many new security issues.The development,characteristics and working principle of SDN were first introduced,and the existing security problems from the application layer,the northbound interface,the control plane,the southbound interface,the data plane were summarized respectively.Secondly,the latest research progress and existing solutions were discussed.Finally,SDN current and future security challenges were summarized,and the future SDN security development direction was looked forward to.